Human (resource)development a conceptual and operational framework for Philippine practitioners.. [article]. - Ortigas, Carmela D.
This articles studies and classifies the human population under three major categories, the dysfunctional-functioning,and highly effective. It describes the processes, strategies which assist these categories of people to move from one point toward higher effectivity, as well as the professionals who help them achieve this movement. It looks at human development from its early efforts of primary care work with the urban and rural poor to the systematic human resource development work in the corporate world. There is special emphasis on the human resource development(HRD) specialists as persons and professionals and the requisites that lead to their becoming effective change agent-managers. All this is integrated in the diagrammatic formulation of a conceptual and operational framework that may be useful to students and practitioners alike. -- (from the author)